A Study on Satisfaction Levels of Working Women Towards Two Wheelers in Coimbatore, Tamil Nadu - Amsaveni, R.; Kokila, R. (Indian Journal of Marketing, 2014)
The two wheeler section in India has witnessed one of the most imposing levels of growth in the automobile industry. The Indian two wheeler market has undergone significant renovation in recent times and stylish, fuel-efficient, and eco-friendly two wheelers are gaining popularity. In addition, the markets in Asia, Africa, Middle East, South America, and even parts of Europe are progressively emerging as new markets for the Indian two wheelers that indicate their enhanced stature and technological prowess. Vehicles are identified as means of logistics and conveyance, a dynamic of livelihood, and even an insignia of wealth and luxury. Women play a significant role in the domestic and social economic life of the society. The prominent role of women in decision making is due to increasing literacy, the ability to be assertive, the possession of independent income, and a more significant role in the family. The present study tries to identify the attributes playing prominent role in the buying behavior of the working women while purchasing two wheelers. The main objective of the study is to comprehend the satisfaction level of working women towards two wheelers and to identify the quandary faced by them. The statistical tools like simple percentage, chi-square test, ANOVA, factor analysis were applied to realize the objectives of the study. The results divulge that majority of the respondents were satisfied with the vehicle they owned; the respondents expected performance, cost effectiveness, appearance, and re-sale value while purchasing two wheelers. The study also reveals that the respondents were facing tribulations like frequent breakdown and low mileage.